Atmospheric lead pollution in a typical megacity: Evidence from lead isotopes - Tao, Zhenghua; Guo, Qingjun; Wei, Rongfei; Dong, Xinyuan; Han, Xiaokun; Guo, Zhaobing (The Science of the total environment, 2021)
Atmospheric lead (Pb) pollution has adverse health effects on humans, while the sources and atmospheric process of Pb are key scientific problems. In this study, the concentrations and isotopic composition of Pb in fine particulate matter (PM2.5), coal and street dust samples collected from a typical megacity Beijing were analyzed to identify the sources of atmospheric Pb. Results showed that the Pb concentrations in PM2.5 were high in winter (168.1 ± 32.0 ng/m3) and low in summer (27.7 ± 9.1 ng/m3), whereas Pb isotopic values presented opposite variation trends. The abnormally elevated Pb concentrations in winter were probably related to coal combustion, while declined Pb concentration in summer may be attributed to favorable meteorological parameters such as high temperature, high wind speed, and frequent rain events. Pb isotopic ratios indicated that anthropogenic sources (coal combustion and vehicle exhaust) and natural sources were the main contributors to Pb in PM2.5. Combined with the binary model, the anthropogenic sources predominantly contributed to Pb in the Beijing atmosphere by approximately 85% annually, while the natural sources accounted for the rest of 15%. More specifically, the contribution of natural sources was about 9.4% in spring, 29.7% in summer, 16.0% in autumn and 6.1% in winter, suggesting that natural sources might contribute more lead into the atmosphere during clear days. Furthermore, the contribution of the vehicle exhaust to atmospheric Pb was nonnegligible in megacity, highlighting that the ownership of motor vehicles in megacity should be regulated and more efforts should be paid to strengthen vehicle emission standard. This study may enrich the reservoir of Pb isotopic composition in nature and provides a new method to investigate the Pb migration and transformation in the environment, and also serve as a theoretical reference for pollution control measures. [Display omitted] •The abnormally elevated Pb concentrations in winter were related to coal heating.•Coal combustion and vehicle exhaust remained important for lead in Beijing.•Natural sources might contribute more lead into the atmosphere during clear days.